Coral bridges : a possible light uptake strategy, by endolithic algae in mesophotic coral ecosystems (2017)
Mesophotic ecosystems are characterized for low light availability, by high water turbidity and/or depth gradient. Under these conditions autotrophic organisms like algae have different strategies to improve the light uptake. Endolithic algae Ostreobium spp. concentrates creating a dark patch to exploit the available light. In these layers appear bridge-like structures between coral costae, which may be a strategy to maximize the light uptake. To prove the presence of Ostreobium spp., bridges sequencing were done using gene rbcL. Besides sequencing, an EDS (energy dispersed X-ray spectroscopy) were used to compare the elemental composition of these structures. The results show that the algae are inside the bridges. The EDS expose clear difference between the bridges and the coral skeleton. Probably the algae are recycling the boring waste to create these structures and uptake light.